Comparative Analysis of the Flavobacterium columnare Genomovar I and II Genomes - Kumru, Salih; Tekedar, Hasan C.; Gulsoy, Nagihan; Waldbieser, Geoffrey C.; Lawrence, Mark L.; Karsi, Attila (Frontiers in Microbiology, 2017)
Columnaris disease caused by Gram-negative rod Flavobacterium columnare is one of the most common diseases of catfish. F. columnare is also a common problem in other cultured fish species worldwide. F. columnare has three major genomovars; we have sequenced a representative strain from genomovar I (ATCC 49512, which is avirulent in catfish) and genomovar II (94-081, which is highly pathogenic in catfish). Here we present a comparative analysis of the two genomes. Interestingly, F. columnare ATCC 49512 and 94-081 meet criteria to be considered different species based on the Average Nucleotide Identity (90.71% similar) and DNA-DNA Hybridization (42.6 % similar). Genome alignment indicated the two genomes have a large number of rearrangements. However, function-based comparative genomics analysis indicated that the two strains have similar functional capabilities with 2263 conserved orthologous clusters; strain ATCC 49512 has 290 unique orthologous clusters while strain 94-081 has 391. Both strains carry type I secretion system (T1SS), type VI secretion system (T6SSiii), and type IX secretion system (T9SS). The two genomes also have similar CRISPR capacities. The F. columnare strain ATCC 49512 genome contains a higher number of insertion sequence families and phage regions, while the F. columnare strain 94-081 genome has more genomic islands and more regulatory gene capacity. Transposon mutagenesis using Tn4351 in pathogenic strain 94-081 yielded six mutants, and experimental infections of fish showed hemolysin and glycine cleavage protein mutants had 15% and 10% mortalities, respectively, while the wild-type strain caused 100% mortalities. Our comparative and mutational analysis yielded important information on classification of genomovars I and II F. columnare as well as potential virulence genes in F. columnare strain 94-081.